ps to regional schools - Lidin, Konstantin (project baikal, 2020)
Provinces and their culture are strongly related to regional architecture schools. In continuation of the topic of the previous issue, we are publishing two articles devoted to complex processes of the genesis of local architecture schools and their relations with geographical (article by P. Kapustin) and historical (article by E. Bagina and M. Arustamyan) peculiarities of the region.